A systematic video analysis of National Hockey League (NHL) concussions, part I: who, when, where and what?. Issue 8 (13th June 2013) - Hutchison, Michael G; Comper, Paul; Meeuwisse, Willem H; Echemendia, Ruben J
Abstract : Background: Although there is a growing understanding of the consequences of concussions in hockey, very little is known about the precipitating factors associated with this type of injury. Aim: To describe player characteristics and situational factors associated with concussions in the National Hockey League (NHL). Methods: Case series of medically diagnosed concussions for regular season games over a 3.5-year period during the 2006–2010 seasons using an inclusive cohort of professional hockey players. Digital video records were coded and analysed using the Heads Up Checklist. Results: Of 197 medically diagnosed concussions, 88% involved contact with an opponent. Forwards accounted for more concussions than expected compared with on-ice proportional representation (95% CI 60 to 73; p=0.04). Significantly more concussions occurred in the first period (47%) compared with the second and third periods (p=0.047), with the majority of concussions occurring in the defensive zone (45%). Approximately 47% of the concussions occurred in open ice, 53% occurred in the perimeter. Finally, 37% of the concussions involved injured players' heads contacting the boards or glass. Conclusions: This study describes several specific factors associated with concussions in the NHL, including period of the game, player position, body size, and specific locations on the ice and particular situations based on a player's position.